Extensive monitoring of forest condition – Level I in Finland - Nevalainen, Seppo; Merilä, Päivi; 4100311110 (The Finnish Forest Research Institute, 2013)
Part of the online report: Merilä, P. & Jortikka, S. (eds.). Forest Condition Monitoring in Finland – National report. The Finnish Forest Research Institute. http://urn.fi/URN:NBN:fi:metla-201305087568.